Phase 1 study of epigenetic priming with decitabine prior to standard induction chemotherapy for patients with AML - Scandura, Joseph M.; Roboz, Gail J.; Moh, Michelle; Morawa, Ewelina; Brenet, Fabienne; Bose, J. Robi; Villegas, Luis; Gergis, Usama S.; Mayer, Sebastian A.; Ippoliti, Cindy M.; Curcio, Tania J.; Ritchie, Ellen K.; et al. (Blood, 2011)
We conducted an open-label phase 1 study exploring the feasibility, safety, and biologic activity of epigenetic priming with decitabine before standard induction chemotherapy in patients with less-than-favorable risk of acute myelogenous leukemia (AML). We directly compared the clinical and DNA-hypomethylating activity of decitabine delivered at 20 mg/m2 by either a 1-hour infusion (Arm A) or a continuous infusion (Arm B) for 3, 5, or 7 days before a single, standard induction with infusional cytarabine (100 mg/m2 for 7 days) and daunorubicin (60 mg/m2 × 3 doses). Toxicity was similar to that of standard induction chemotherapy alone. Although we did not identify a maximum tolerated dose, there was more gastro-intestinal toxicity with 7 days of decitabine priming. Decitabine induced DNA hypomethylation at all dose levels and there was a trend toward greater hypomethylation in CD34+ bone marrow cells when decitabine was delivered by a short pulse (Arm A). Twenty-seven subjects (90%) responded to therapy: 17 with complete remission (57%) and 10 with partial remission (33%). Of the patients with partial remission to protocol treatment, 8 achieved remission to their next therapy, bringing the overall complete remission rate to 83%. We conclude that epigenetic priming of intensive chemotherapy can be safely delivered in an attempt to improve response rates. This trial was registered at www.clinicaltrials.gov as NCT00538876.